MEANING ANALAYSIS AND DYNAMIC EQUIVALANCE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Dynamic equivalence, as a translation principle, aims to recreate the impact of the source text on the target audience. Meaning analysis serves as the foundation for achieving this equivalence. By meticulously examining the source text's semantic and pragmatic aspects, translators gain a deep understanding of its intended meaning. This understanding empowers them to make informed choices in the target language, ensuring that the translated text conveys the original message accurately and effectively while respecting cultural nuances and achieving naturalness of expression.